An APC:WNT Counter-Current-Like Mechanism Regulates Cell Division Along the Human Colonic Crypt Axis: A Mechanism That Explains How APC Mutations Induce Proliferative Abnormalities That Drive Colon Cancer Development - Boman, Bruce M.; Fields, Jeremy Z. (Frontiers in Oncology, 2013)
APC normally down-regulates WNT signaling in human colon, and APC mutations cause proliferative abnormalities in premalignant crypts leading to colon cancer, but the mechanisms are unclear at the level of spatial and functional organization of the crypt. Accordingly, we postulated a counter-current-like mechanism based on gradients of factors (APC;WNT) that regulate colonocyte proliferation along the crypt axis. During crypt renewal, stem cells (SCs) at the crypt bottom generate non-SC daughter cells that proliferate and differentiate while migrating upwards. The APC concentration is low at the crypt bottom and high at the top (where differentiated cells reside). WNT signaling, in contrast, is high at the bottom (where SCs reside) and low at the top. Given that WNT and APC gradients are counter to one another, we hypothesized that a counter-current-like mechanism exists. Since both APC and WNT signaling components (e.g. survivin) are required for mitosis, this mechanism establishes a zone in the lower crypt where conditions are optimal for maximal cell division and mitosis orientation (symmetric versus asymmetric). APC haploinsufficiency diminishes the APC gradient, shifts the proliferative zone upwards, and increases symmetric division, which causes SC overpopulation. In homozygote mutant crypts, these changes are exacerbated. Thus, APC-mutation-induced changes in the counter-current-like mechanism cause expansion of proliferative populations (SCs, rapidly-proliferating cells) during tumorigenesis. We propose this mechanism also drives crypt fission, functions in the crypt cycle, and underlies adenoma development. Novel chemoprevention approaches designed to normalize the two gradients and readjust the proliferative zone downwards, might thwart progression of these premalignant changes.